Case report: A study on disease diagnosis and treatment outcome of a case of bilateral malignant solitary fibrous tumor of the kidneys - Cui, Yujie; Li, Bingjie; Liang, Jinlong; He, Liya; Zhang, Hongzhen (Frontiers in Oncology, 2025)
Solitary fibrous tumor (SFT) is widely present in human connective tissues. It is mostly found in the pleura and other extrapleural sites. There is limited literature on malignant SFT in the retroperitoneum. In this study, we retrospectively reviewed the clinical data of a case of bilateral malignant SFT patient admitted to our hospital in May 2021.The patient had a huge tumor load and multiple bone metastases at the first diagnosis. Due to the need for lifelong hemodialysis after double nephrectomy and multiple bone metastases, the patient gave up surgical treatment, underwent drug treatment, and finally survived for 30 months.